2018
DOI: 10.1038/s41467-017-02776-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-arrestin recruitment and reduced desensitization by non-catechol agonists of the D1 dopamine receptor

Abstract: Selective activation of dopamine D1 receptors (D1Rs) has been pursued for 40 years as a therapeutic strategy for neurologic and psychiatric diseases due to the fundamental role of D1Rs in motor function, reward processing, and cognition. All known D1R-selective agonists are catechols, which are rapidly metabolized and desensitize the D1R after prolonged exposure, reducing agonist response. As such, drug-like selective D1R agonists have remained elusive. Here we report a novel series of selective, potent non-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
179
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(190 citation statements)
references
References 68 publications
11
179
0
Order By: Relevance
“…Although the in vivo data strongly support the hypothesis that dihydrexidine is a full agonist at Gα OLF mediated signaling, the question may be worthy of additional study, especially as a highly-biased D 1 partial agonist recently was reported to be effective in PD (Papapetropoulos et al, 2018). Interestingly, Interestingly, thee new clinical D 1 agonist candidates are not all full agonists, but are functionally selective with no D 1 mediated β -arrestin2 recruiting activity (Gray et al, 2018).…”
Section: Intrinsic Pharmacological Issuesmentioning
confidence: 88%
“…Although the in vivo data strongly support the hypothesis that dihydrexidine is a full agonist at Gα OLF mediated signaling, the question may be worthy of additional study, especially as a highly-biased D 1 partial agonist recently was reported to be effective in PD (Papapetropoulos et al, 2018). Interestingly, Interestingly, thee new clinical D 1 agonist candidates are not all full agonists, but are functionally selective with no D 1 mediated β -arrestin2 recruiting activity (Gray et al, 2018).…”
Section: Intrinsic Pharmacological Issuesmentioning
confidence: 88%
“…Such cationic molecules are almost canonical for these on-targets, but this is a feature shared with H 1 ligands. Allowing for nonaminergic ligands, which are very rare for this family of receptor but not entirely unheard of, 69 or expanding our search to putative allosteric sites where sequence diversity is higher 59 may have improved our chances of finding selective ligands, though it would likely have reduced hit-rates against the on-targets themselves. Finally, our failure to reliably select against the antitargets at least partly reflects well-known weaknesses in our methods.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…NY0128 at 10 μmol/L displayed a significant inverse agonism, further indicating the ligands are not NMUR2 agonists via beta‐arrestins. Since beta‐arrestin recruitment often promotes receptor desensitization resulting in decreased G protein signaling, this general lack of beta‐arrestin activity by NY0128 and NY0116 could be an important factor supporting sustained agonist activity at NMUR2 to ultimately drive weight‐loss during prolonged drug treatments. Taken together, these results suggest NY0116 and NY0128 are NMUR2 agonists for G i ‐mediated cAMP inhibition and G q ‐mediated calcium signaling and have undetectable and/or weak potency for beta‐arrestin recruitment.…”
Section: Discussionmentioning
confidence: 99%